No pain, no gain revisited: the impact of positive and negative psychotherapy experiences on treatment outcome - Verkooyen, Roos; Broers, Nick J.; Dandachi-FitzGerald, Brechje (Frontiers in Psychology, 2024)
Objective: Psychotherapy may have many benefits for patients with mental health problems, but patients may also have negative experiences related to the therapy. Not much is known about these negative psychotherapy experiences and their impact on treatment outcome. The aim of this study was to examine the association between positive and negative psychotherapy experiences and treatment outcome. Methods: A total of 131 patients participated in the study. They received treatment as usual and were assessed for positive and negative psychotherapy experiences at mid-treatment and post-treatment using the Positive and Negative Experiences of Psychotherapy Questionnaire (PNEP). Treatment outcome was measured by the Outcome Questionnaire -45 (OQ-45).Multiple linear regression was used to analyze the data.Results: All patients reported positive psychotherapy experiences at mid-treatment. At least one negative experience was reported by 69% of participants. After correction for baseline severity (i.e., OQ-45 at baseline) and relevant demographic variables, positive psychotherapy experiences at mid-treatment emerged as a predictor for treatment outcome. In contrast, negative psychotherapy experiences did not predict treatment outcome. However, reporting more negative experiences was associated with reporting fewer positive experiences at midand end of treatment.Both positive and negative psychotherapy experiences commonly occur.Although in this study negative psychotherapy experiences did not predict treatment outcome in terms of symptom reduction, the findings do suggest that negative experiences may influence the way in which patients evaluate their treatment. Although positive experiences outweigh negative experiences, patients should be informed that negative experiences may also occur.